2013
DOI: 10.3389/fendo.2013.00036
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Roles of Neurotensin Agonists in the Central Nervous System

Abstract: Neurotensin (NT) is a tridecapeptide that is found in the central nervous system (CNS) and the gastrointestinal tract. NT behaves as a neurotransmitter in the brain and as a hormone in the gut. Additionally, NT acts as a neuromodulator to several neurotransmitter systems including dopaminergic, sertonergic, GABAergic, glutamatergic, and cholinergic systems. Due to its association with such a wide variety of neurotransmitters, NT has been implicated in the pathophysiology of several CNS disorders such as schizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(132 citation statements)
references
References 256 publications
3
95
0
Order By: Relevance
“…administration. In addition, the analgesic activities of systemically administered ANG2002 in models of nociception were very similar to those of centrally administered NT (22)(23)(24)(25). Finally, the hypotensive and hypothermogenic responses, which were previously reported for the NT peptide (46,47), were not observed with the low analgesic dose of ANG2002.…”
Section: Figurementioning
confidence: 71%
See 3 more Smart Citations
“…administration. In addition, the analgesic activities of systemically administered ANG2002 in models of nociception were very similar to those of centrally administered NT (22)(23)(24)(25). Finally, the hypotensive and hypothermogenic responses, which were previously reported for the NT peptide (46,47), were not observed with the low analgesic dose of ANG2002.…”
Section: Figurementioning
confidence: 71%
“…We also showed that ANG2002 bound to NTS1 and NTS2 receptors in the low nanomolar range, thus exhibiting a similar binding affinity to that of native NT. We further found that ANG2002 and NT were equally effective in inducing β-arrestin2 recruitment, G protein functional coupling, and second effects reported in the use of chronic opioid medications (22)(23)(24)(25). However, the approach described in this work substantially differs from other approaches taken in the past for NT therapeutics, most notably those that explored the utility of chemically modifying NT fragments (typically consisting of the 6 C-terminal amino acids of the peptide) as a means of allowing systemic administration.…”
Section: Figurementioning
confidence: 85%
See 2 more Smart Citations
“…In the brain, NT interacts with different neurotransmitter systems, and is involved in the central control of appetite, endocrine functions, pain modulation, and pathogenesis of mental disorders (Boules et al, 2013). High amounts of NT are also present in endocrine-like cells localized in intestinal mucosa, whereby NT is released upon food intake, and contributes to regulation of gastrointestinal motility and secretion (Kalafatakis and Triantafyllou, 2011).…”
Section: Introductionmentioning
confidence: 99%